Democracy Crisis in South-East Asia: Media Control, Censorship, and Disinformation during the 2019 Presidential and General Elections in Indonesia, Thailand and 2019 Local Election in the Philippines - Aniello Iannone (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
South-East Asia is suffering a rapid deterioration of the free press and Freedom of expression. According to the last report of Freedom in the World 2021, in the last few years, almost all the South-East Asian countries have experienced a reduction in Freedom of expression, and in certain cases, their rights have been restricted. What kind of effects do the media have on public opinion? How can disinformation, censorship, and media control manipulate public opinion? Is social media promoting the anti-democracy establishment? Does social media reduce the democratic quality of a country by limiting its expression through control? This paper is based on desk-based research, where literature on political history and the political history of using media has been reviewed and analyzed—with a comparative analysis, focusing on the data available on the three countries of interest: Indonesia, Thailand, and the Philippines, taking a comparative study the last election in 2019 in those countries. As a method, this study conducts a critical literature review with a historical approach. This study found that all the countries analyzed utilized the media to spread disinformation, war propaganda, and control. Borrowing from the Gramscian theory of hegemony, the paper argues that the theory of media and control can be used as a theoretical framework to examine the rule of media to manipulate and control the public opinion.